The HALP (hemoglobin, albumin, lymphocyte, and platelet) score is associated with hemorrhagic transformation after intravenous thrombolysis in patients with acute ischemic stroke - Chen, Jiahao; Hu, Rui; Shang, Lejia; Li, Xiaoqin; Lin, Yisi; Yao, Yu; Hu, Chuanchen (Frontiers in Neurology, 2024)
BackgroundHemorrhagic transformation (HT) after intravenous thrombolysis (IVT) with rt-PA can precipitate rapid neurological deterioration, poor prognosis, and even death. The HALP score (hemoglobin, albumin, lymphocyte, and platelet) is a novel indicator developed to reflect both systemic inflammation and the nutritional status of patients. The goal of this study was to reveal the relationship between the HALP score and the risk of HT after IVT in people with acute ischemic stroke (AIS).MethodsA total of 753 patients with AIS were included in this study. Patients were divided into quartiles according to baseline HALP score. The HALP score was calculated as follows: hemoglobin (g/L) × albumin (g/L) × lymphocytes (/L)/platelets (/L). Binary logistic regression was used to reveal the connection between HALP score and HT.ResultsThe baseline HALP score were significantly lower in the HT than non-HT patients (p < 0.001). The HALP score were divided into four quartiles: Q1 (<27.4), Q2 (27.4–37.6), Q3 (37.7–49.6), Q4 (>49.6), respectively. Moreover, the severity of HT increased with decreasing HALP level (p < 0.001). In multivariable logistic regression, taking the Q4 as the reference, the association between Q1 and HT remained, after adjusting for confounding variables [odds ratio (OR) = 3.197, 95% confidence interval (CI) = 1.634–6.635, p = 0.003].ConclusionThe HALP value can predict the HT risk after IVT in patients with AIS. A lower HALP level was associated with an increased severity of HT post-IVT.